2021
DOI: 10.3748/wjg.v27.i15.1531
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cytokine storm and systemic inflammation on liver impairment patients infected by SARS-CoV-2: Prospective therapeutic challenges

Abstract: Coronavirus disease 2019 (COVID-19) is a devastating worldwide pandemic infection caused by a severe acute respiratory syndrome namely coronavirus 2 (SARS-CoV-2) that is associated with a high spreading and mortality rate. On the date this review was written, SARS-CoV-2 infected about 96 million people and killed about 2 million people. Several arguments disclosed the high mortality of COVID-19 due to acute respiratory distress syndrome or change in the amount of angiotensin-converting enzyme 2 (ACE2) receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 212 publications
0
14
0
Order By: Relevance
“…The systemic inflammatory response syndrome, particularly the cytokine storm, is one of the key pathophysiologic processes behind the development of severe disease in COVID-19 [ 50 ]. The presence of fibrosis may worsen the virus-induced cytokine storm and add to the severity of COVID-19 by the production of proinflammatory cytokines from the liver [ 51 ]. However, further research is required to investigate the pathways through which advanced liver fibrosis contributes to the COVID-19 pathological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The systemic inflammatory response syndrome, particularly the cytokine storm, is one of the key pathophysiologic processes behind the development of severe disease in COVID-19 [ 50 ]. The presence of fibrosis may worsen the virus-induced cytokine storm and add to the severity of COVID-19 by the production of proinflammatory cytokines from the liver [ 51 ]. However, further research is required to investigate the pathways through which advanced liver fibrosis contributes to the COVID-19 pathological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“… 20 COVID-19 patients infected with SARS-CoV-2 with an impaired liver function exhibit ACE2 receptor overexpression and cytokine storm overexpression, which ultimately exacerbates liver function impairment and mortality. 21 In our study, individual patients with liver function impairment were mainly distinguished by elevated GGT and/or TB. GGT is a standard liver enzyme test which reflects the involvement of the biliary tract.…”
Section: Discussionmentioning
confidence: 60%
“…However, there are few reports on the severity of hepatic impairment, clinical outcome and mortality rate in patients with different chronic liver diseases co-infected with SARS-CoV-2. Ali et al [ 6 ] summarized the remarkable impact of SARS-CoV-2 on several types of liver diseases, including non-alcoholic fatty liver disease), liver cirrhosis, hepatocellular carcinoma, and hepatitis B and C virus infection. Furthermore, they reviewed the devastating cytokine storm in COVID-19 and concluded that in a similar pattern, hepatic impairment patients co-infected with SARS-CoV-2 could exhibit overexpression of ACE2 receptors and overwhelming cytokine storm, which might worsen the hepatic impairment and increases the mortality rate.…”
Section: To the Editormentioning
confidence: 99%